Adverse postoperative cognitive disorders: a national survey of portuguese anesthesiologists - Susano,Maria J. (2018)
Abstract Background and objectives Postoperative delirium and postoperative cognitive dysfunction are some of the most common complications in older surgical patients and are associated with adverse outcomes. The aim of this study was to evaluate portuguese anesthesiologists’ perspectives and knowledge about adverse postoperative cognitive disorders, and routine clinical practice when caring for older surgical patients. Methods We used a prospective online survey with questions using a Likert scale from 1 to 5 (completely disagree to completely agree), or yes/no/don’t know answer types. Potential participants were portuguese anesthesiologists working in hospitals affiliated with the portuguese national health system and private hospitals. Results We analyzed 234 surveys (17.7% of total potential respondents). The majority believed that the risk of cognitive side effects should be considered when choosing the type of anesthesia (87.6%) and that preoperative cognitive function should be routinely assessed (78.6%). When caring for an agitated and confused patient postoperatively, 62.4% would first administer an analgesic and 11.1% an anxiolytic. Protocols to screen and manage postoperative cognitive disorders are rarely used. Nearly all respondents believe that postoperative delirium and postoperative cognitive dysfunction are neglected areas in anesthesiology. Conclusions Overall, participants perceive postoperative cognitive disorders as important adverse outcomes following surgery and anesthesia are aware of the main risk factors for their development but may lack information on prevention and management of postoperative delirium. The majority of hospitals do not have protocols regarding preoperative cognitive assessment, diagnosis, management or follow-up of patients with delirium and postoperative cognitive dysfunction.